The Effects of Using Nature Audiovisual Record Accompany By Surah Yasin into Soul Calmness - Yusof, Siti Fuziah (2008)
study is to drive a method that can be used by the Muslim to increase their calmness when they are in stress. Life without al-Qur’an’s guidance must be avoided and usage of audiovisual recording can be implemented. It is important to prove that by viewing nature with perception of Allah (s.w.t.) through al-Qur’an will greatly increase calmness compare to viewing nature by it self. An Investigation Method was performed in Klang Valley to collect comparative data of 2 audiovisual recordings that show the nature’s view with their sound compare with the audiovisual that shown the nature’s views with Surah Yasi@n. The significant difference value from T-Test Paired Sampling is 0.00, while the result from Descriptive Test and T-Test Sampling proved that responses from Surah Yasi@n increased more calmness when viewing nature with it. Correlation Test also proved that there were positive relations between the inclination to Allah (s.w.t.) and Islam with calmness. With the Hypothesis accepted and supported by experts, the recording of audiovisual can be proposed as the method of Muslim’s soul treatment.